Single Enzyme Nanoparticles with Improved Biocatalytic Activity through Protein Entrapment in a Surfactant Shell - Atkins, Dylan L. (Biomacromolecules, 2021)
[Image: see text] A polymeric corona consisting of an alkyl-glycolic acid ethoxylate (C(X)EO(Y)) surfactant offers a promising approach toward endowing proteins with thermotropic phase behavior and hyperthermal activity. Typically, preparation of protein–surfactant biohybrids is performed via chemical modification of acidic residues followed by electrostatic conjugation of an anionic surfactant to encapsulate single proteins. While this procedure has been applied to a broad range of proteins, modification of acidic residues may be detrimental to function for specific enzymes. Herein, we report on the one-pot preparation of biohybrids via covalent conjugation of surfactants to accessible lysine residues. We entrap the model enzyme hen egg-white lysozyme (HEWL) in a shell of carboxyl-functionalized C(12)EO(10) or C(12)EO(22) surfactants. With fewer surfactants, our covalent biohybrids display similar thermotropic phase behavior to their electrostatically conjugated analogues. Through a combination of small-angle X-ray scattering and circular dichroism spectroscopy, we find that both classes of biohybrids consist of a folded single-protein core decorated by surfactants. Whilst traditional biohybrids retain densely packed surfactant coronas, our biohybrids display a less dense and heterogeneously distributed surfactant coverage located opposite to the catalytic cleft of HEWL. In solution, this surfactant coating permits 7- or 3.5-fold improvements in activity retention for biohybrids containing C(12)EO(10) or C(12)EO(22), respectively. The reported alternative pathway for biohybrid preparation offers a new horizon to expand upon the library of proteins for which functional biohybrid materials can be prepared. We also expect that an improved understanding of the distribution of tethered surfactants in the corona will be crucial for future structure–function investigations.